Sphingosine-1 phosphate induces cAMP/PKA-independent phosphorylation of the cAMP response element-binding protein (CREB) in granulosa cells. (15th January 2021) - Paradiso, Elia; Lazzaretti, Clara; Sperduti, Samantha; Antoniani, Francesco; Fornari, Giulia; Brigante, Giulia; Di Rocco, Giulia; Tagliavini, Simonetta; Trenti, Tommaso; Morini, Daria; Falbo, Angela Immacolata; Villani, Maria Teresa; et al.
Abstract: Background and aims: Sphingosine-1 phosphate (S1P) is a lysosphingolipid present in the ovarian follicular fluid. The role of the lysosphingolipid in gonads of the female is widely unclear. At nanomolar concentrations, S1P binds and activates five specific G protein-coupled receptors (GPCRs), known as S1P1-5, modulating different signaling pathways. S1P1 and S1P3 are highly expressed in human primary granulosa lutein cells (hGLC), as well as in the immortalized human primary granulosa cell line hGL5. In this study, we evaluated the signaling cascade activated by S1P and its synthetic analogues in hGLC and hGL5 cells, exploring the biological relevance of S1PR-stimulation in this context. METHODS AND RESULTS. hGLC and hGL5 cells were treated with a fixed dose (0.1 μM) of S1P, or by S1P1 - and S1P3 -specific agonists SEW2871 and CYM5541. In granulosa cells, S1P and, at a lesser extent, SEW2871 and CYM5541, potently induced CREB phosphorylation. No cAMP production was detected and pCREB activation occurred even in the presence of the PKA inhibitor H-89. Moreover, S1P-dependent CREB phosphorylation was dampened by the mitogen-activate protein kinase (MEK) inhibitor U0126 and by the L-type Ca 2+ channel blocker verapamil. The complete inhibition of CREB phosphorylation occurred by blocking either S1P2 or S1P3 with the specific receptor antagonists JTE-013 and TY52156, or under PLC/PI3K depletion. S1P-dependent CREB phosphorylation induced FOXO1 and the EGF-like epiregulin-encoding gene ( EREG ), confirming the exclusive role of gonadotropins and interleukins in this process, but did not affect steroidogenesis. However, S1P or agonists did not modulate granulosa cell viability and proliferation in our conditions. Conclusions: This study demonstrates for the first time that S1P may induce a cAMP-independent activation of pCREB in granulosa cells, although this is not sufficient to induce intracellular steroidogenic signals and progesterone synthesis. S1P-induced FOXO1 and EREG gene expression suggests that the activation of S1P–S1PR axis may cooperate with gonadotropins in modulating follicle development. Highlights: S1P potently stimulates CREB phosphorylation in human granulosa cells. S1P-induced CREB phosphorylation is independent of cAMP/PKA pathway. The production of progesterone is not affected by S1P in granulosa cells.